2013
DOI: 10.2174/1568026611313020002
|View full text |Cite
|
Sign up to set email alerts
|

NTproBNP: An Important Biomarker in Cardiac Diseases

Abstract: Natriuretic neuropeptides (ANP, BNP, CNP) are produced primarily in the cardiac atria under normal conditions. The main stimulus for ANP and BNP peptide synthesis and secretion is cardiac wall stress. Cardiac ventricular myocytes constitute the major source of BNP-related peptides. Ventricular NT-proBNP production is upregulated in cardiac failure and locally in the area surrounding a myocardial infarct. NT-proBNP is cleared passively by organs with high rate of blood flow (muscle, liver, kidney). It has a lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 0 publications
4
79
0
3
Order By: Relevance
“…Recent studies have suggested that monitoring the BNP level could aid in the early diagnosis of chronic cardiac failure and serve as an indicator of the curative effects of treatment and prognosis. Patients with more serious disease had higher BNP levels [21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies have suggested that monitoring the BNP level could aid in the early diagnosis of chronic cardiac failure and serve as an indicator of the curative effects of treatment and prognosis. Patients with more serious disease had higher BNP levels [21].…”
Section: Discussionmentioning
confidence: 94%
“…21.0 software; all data were expressed as mean ± standard deviations (SD). The paired t-test was used to compare data obtained before and after treatment, and between-group comparisons were made using the two-sample t-test.…”
Section: Discussionmentioning
confidence: 99%
“…Brain natriuretic peptide (BNP) belongs to a group of vasodilator and anti-proliferative neurohormonal natriuretic polypeptides that are produced primarily by the cardiac ventricles (and in lesser amounts by the brain and adrenal glands) in response to stretching of cardiac myocytes or increased cardiac wall stress [139]. ProBNP, a biologically inactive prohormone, is secreted by the ventricles in response to ventricular dysfunction and cleaved into the physiologically active BNP and the biologically inactive N-terminal fragment (NTproBNP) [139].…”
Section: Brain Natriuretic Peptides: a Marker Of Cardiovascular Riskmentioning
confidence: 99%
“…ProBNP, a biologically inactive prohormone, is secreted by the ventricles in response to ventricular dysfunction and cleaved into the physiologically active BNP and the biologically inactive N-terminal fragment (NTproBNP) [139]. BNP has a half-life of approximately 20 min, and is cleared actively and passively through the renal system.…”
Section: Brain Natriuretic Peptides: a Marker Of Cardiovascular Riskmentioning
confidence: 99%
See 1 more Smart Citation